Biomimetic Materials: Bacterially Produced, Nacre‐Inspired Composite Materials (Small 22/2019). Issue 22 (29th May 2019) - Spiesz, Ewa M.; Schmieden, Dominik T.; Grande, Antonio M.; Liang, Kuang; Schwiedrzik, Jakob; Natalio, Filipe; Michler, Johann; Garcia, Santiago J.; Aubin‐Tam, Marie‐Eve; Meyer, Anne S.
Abstract : In article number1805312, Marie‐Eve Aubin‐Tam, Anne S. Meyer, and co‐workers use bacteria to produce nacre‐inspired composite materials that exhibit high toughness and stiffness, along with impressive extensibility. The extensive diversity of bacterial metabolic abilities and the possibility of genetic engineering will allow for creating a library of cost‐effective, eco‐friendly composite materials.